A systematic experimental investigation on the synergistic effects of aqueous nanofluids on interfacial properties and their implications for enhanced oil recovery. (15th May 2018) - Kuang, Wendi; Saraji, Soheil; Piri, Mohammad
Abstract: Nanofluids have been proposed as potential enhanced oil recovery agents and additives to hydraulic fracturing fluids. The underlying mechanisms responsible for effectiveness of these fluids, however, are not well understood. In this study, we experimentally investigate synergistic effects of aqueous nanofluids on interfacial properties of oil/brine/rock systems and their role in influencing oil displacement from sandstone and carbonate rock samples. The nanofluids were prepared by dispersing three widely-used nanoparticles (i.e., SiO x, Al 2 O 3, and TiO 2 ) and five different chemical agents (i.e., oleic acid, polyacrylic acid, a cationic, an anionic, and a nonionic surfactant) in base brine solutions. The efficacy of the mixtures was examined using a framework that including a comprehensive stability analysis, IFT and wettability characterizations, and oil recovery tests at ambient as well as high pressure and high temperature conditions (i.e., spontaneous imbibition and core-flooding experiments, respectively). Effects of stable nanofluids, identified from stability analysis, on interfacial tension and dynamic contact angle were carefully investigated. We show that co-adsorption and self-structuring of nanoaggregates and chemical agents at the solid interface leads to wettability alteration. Both spontaneous imbibition and high pressure and high temperature core-flooding results reveal the effectiveness of SiO x + nonionic surfactant nanofluid in enhancing oil recovery in Berea sandstone due to a synergistic effect between nanoparticles and surfactant molecules. In contrast, the stability of nanofluids was highly compromised in Edwards limestone due to dissolution and interaction of calcium ions with nanoaggregates at high temperature. This was evident in the drastic difference between oil recoveries obtained through ambient-temperature spontaneous imbibition and high-temperature core-flooding experiments conducted on carbonate core samples. Finally, we provide new insights on interfacial interactions in nanofluid/oil/rock systems as they relate to wettability alteration, IFT reduction, and the effect of dissolved ions such as calcium in carbonate rocks. We use this improved understanding to explain the recovery trends observed in our study.